LINGUISTIC STYLE ON AUDIENCE ENGAGEMENT: A STUDY OF MICRO-INFLUENCER CONTENT - Linda, Linda (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study investigates Linguistic style on audience engagement in the context of micro-influencer content on social media platforms. Micro-influencers, characterized by their relatively small but highly engaged follower base, often leverage unique linguistic styles to connect with their audience. Through a mixed-methods approach combining quantitative content analysis and qualitative discourse analysis, this research examines a sample of micro-influencer posts across various social media channels. The study aims to identify key linguistic features that correlate with higher levels of audience engagement, defined through metrics such as likes, comments, shares, and follower growth. By analyzing variables such as tone, formality, use of slang, and the presence of narrative elements, the research seeks to uncover patterns that contribute to effective communication strategies. Preliminary findings suggest that a conversational tone, inclusive language, and the strategic use of personal anecdotes significantly enhance audience interaction. Additionally, posts that balance authenticity with promotional content tend to foster greater trust and loyalty among followers. The study contributes to the growing body of literature on digital marketing and influencer communication by providing actionable insights for micro-influencers and marketers aiming to optimize their content for better audience engagement.